Perempuan di Panggung Kekuasaan: Menelusuri Asumsi Publik dan Wacana Gender dan Kepemimpinan Pemerintahan - Ginting, Abdul Fikri; Sazali, Hasan; Sayekti, Retno (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to uncover how the views of religious figures and political figures shape public assumptions towards women’s leadership in government The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with purposively selected religious and political figures. These two groups were chosen because of their important role in shaping opinions and influencing social discourse in society.The results show that the discourse on women’s leadership is still largely overshadowed by conservative religious interpretations and deeply rooted patriarchal social constructs Religious figures generally express caution or even reject women’s leadership, referring to normative textsunderstood literally. Meanwhile, the views of political figures are more diverse—some openly support it based on women’s capacity and contribution in government, while others still view women as symbolic complements in politics.Public discourse on women’s leadership is largely determined by the legitimacy granted by religious and political figures When these two authorities tend to maintain traditional gender interpretations, the opportunities for women to be substantively accepted in leadership become limited. Therefore, reconstructing the discourse and the active involvement of these figures in promoting narratives of equality are key to opening up a more inclusive and gender-just space for power.